Criminal liturgy in colonial justice - Garcés, Carlos Alberto (2008)
In its penal ceremonies, colonial justice proceeds according to a liturgical order, a pre-established, quasi-religious ritual, canonized by a particular social tradition. The liturgical order is followed as a logical rule in the punitive procedure: in the face of the breach of a norm, justice, as its antagonist, represses the fact through punishment. It is the fundamental opposition of criminal law: crime and punishment. The ultimate foundation of the power to apply punishment lies in the transgression whose delimitation is exhaustively predetermined. The ritual of colonial justice then follows a liturgical order that regulates times and spaces in such a way that they make sense for society. In this work, these rituals are analyzed, which establish a series of sequences or steps from the capture of the transgression to the final application of the punishment. The material and symbolic components and the discursive sequence of the penal ritual will be studied.